Peliosanthes multiflora (Asparagaceae), a small-flowered new species from Vietnam - Kroupsky, Ivan A.; Lyskov, Dmitry F.; Romanov, Mikhail S.; Drokina, Victoria G.; Dac, Le Xuan; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Nguyen, Khang Sinh; Tanaka, Noriyuki; Nuraliev, Maxim S. (Phytotaxa, 2025)
Peliosanthes multiflora, a new species of Asparagaceae, is described and illustrated. The species was discovered in 2021 in Phu Yen Province, southern Vietnam. Peliosanthes multiflora differs from its congeners in having narrowly elliptic to linear leaf blades, reflexed to recurved perianth lobes, and exceptionally many-flowered inflorescences strongly exceeding the leaves. Each of these traits is rare in the genus. A feature useful for the field recognition of P. multiflora is the remarkably small size of its fully open flowers, which is a result of the small flower parts combined with the reflexed perianth lobes.